2021
DOI: 10.1007/s13311-020-00953-z
|View full text |Cite
|
Sign up to set email alerts
|

A Nitroalkene Benzoic Acid Derivative Targets Reactive Microglia and Prolongs Survival in an Inherited Model of ALS via NF-κB Inhibition

Abstract: Motor neuron degeneration and neuroinflammation are the most striking pathological features of amyotrophic lateral sclerosis (ALS). ALS currently has no cure and approved drugs have only a modest clinically therapeutic effect in patients. Drugs targeting different deleterious inflammatory pathways in ALS appear as promising therapeutic alternatives. Here, we have assessed the potential therapeutic effect of an electrophilic nitroalkene benzoic acid derivative, (E)-4-(2-nitrovinyl) benzoic acid (BANA), to slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Interestingly, the role of lactic acid derivatives as signaling molecules in the brain with possible neuroprotective effects is increasingly being pointed out [ 33 ], as is the possibility of using lactic acid bacteria in an animal model of Alzheimer’s disease [ 34 ]. Furthermore, the neuroprotective properties of benzoic and acetic acid derivatives have also prompted preclinical trials of their therapeutic use in various neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) or multiple sclerosis (MS) [ 35 , 36 ], and even applications in DM-induced and Parkinson’s disease (PD)-related neurodegeneration [ 37 ]. It should be noted that the results of metabolic studies can be applied not only in the search for markers of observed disorders, but also as therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the role of lactic acid derivatives as signaling molecules in the brain with possible neuroprotective effects is increasingly being pointed out [ 33 ], as is the possibility of using lactic acid bacteria in an animal model of Alzheimer’s disease [ 34 ]. Furthermore, the neuroprotective properties of benzoic and acetic acid derivatives have also prompted preclinical trials of their therapeutic use in various neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) or multiple sclerosis (MS) [ 35 , 36 ], and even applications in DM-induced and Parkinson’s disease (PD)-related neurodegeneration [ 37 ]. It should be noted that the results of metabolic studies can be applied not only in the search for markers of observed disorders, but also as therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should also be noted that once paeoniflorin enters into the body, it can be converted into another molecule that crosses the blood-brain barrier, benzoic acid ( Yu et al, 2019b ). Benzoic acid supplementation can improve cognitive function in patients with schizophrenia ( Lane et al, 2013 ), dementia ( Lin et al, 2019 ; Lin et al, 2021 ), and early-phase Alzheimer’s disease ( Lin et al, 2014 ), and benzoic acid derivatives have been reported to exert numerous pharmacological effects in the nervous system, such as suppression of glaucoma-associated neurodegeneration ( Luo et al, 2020 ), inhibition of microglial activation and pathological processes of amyotrophic lateral sclerosis ( Ibarburu et al, 2021 ), and inhibition of proliferation of human glioma cells ( Yue et al, 2016 ), researchers should clarify whether the pharmacological effects of paeoniflorin in the central nervous system are mediated by benzoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds providing protection against apoptosis and motor neurone degeneration: sphingosine-1-phosphate [24], metformin [31], thymoquinone [44], citicoline [45], nitrovinyl benzoic acid (4-[(1E)-2-nitrovinyl] benzoic acid) [46], ambroxol [47], isofagomine [47], fingolimod [47], fasudil [48], Y-27632 [48], acerogenin [49]. Xanomeline [16], telmisartan [37], orientin [50], geniposide [51], licochalcone A [52], taraxasterol [53], acetylcarnitine [54], atorvastatin [55], riluzole [56] and sulforaphane [57] protect neurons against oxygen-glucose deprivation/reperfusion.…”
Section: Compound Structuresmentioning
confidence: 99%